Does Using In-Copyright Works as Training Data Infringe? - Samuelson, Pamela (Communications of the ACM, 2025)
The article discusses the legal aspects of copyrights in relation to generative artificial intelligence (GenAI) developments, and it mentions copyright infringement claims involving the use of in-copyright materials in GenAI training data. The copyright court cases Bartz v. Anthropic and Kadrey v, Meta are assessed, as well as copyright's fair use doctrine, legal defenses, and, copyright-related piracy of books. Lost sales and market dilution are addressed.